A comprehensive review on the application of evolutionary computation in design optimization of plate-fin heat exchangers - Yousefi M.; Yousefi M.; Khaksar W.; Ismail Alnaimi F.B.; Darus A.N. (Praise Worthy Prize, 2023)
This review study presents the utilization of different evolutionary algorithms (EAs) for plate-fin heat exchanger (PFHE) design optimization in the last decade. The traditional trialand- error design process of CHEs can be replaced by a more flexible and easy-to-implement evolutionary approach. EAs do need any information of derivatives and therefore can be implemented in a wide range of applications without much effort. Many EAs have been successfully presented and employed in various fields of engineering including heat transfer problems and more specifically CHE design optimization. However there seems to be gap in the literature regarding analyses of pros and cons of these algorithms for use in this field. This study could be useful for future use of EAs in not only CHE design optimization but also for the whole field of heat exchanger. 2015 Praise Worthy Prize S.r.l. - All rights reserved.